2024
DOI: 10.21608/ejvs.2024.252030.1691
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Resistance and Pathogenicity Genes of E. coli Isolated From Broiler Chicken Farms

Ahmed Ahmed,
Heba Salem,
Mohamed Hamoud
et al.

Abstract: scherichia coli (E. coli) is a widespread avian pathogen and usually is considered as a secondary pathogen for different infectious agents causing huge financial losses in the poultry industry. Thus, the current works aim to molecular detection of resistance and pathogenicity genes of E. coli isolated from broiler chicken farms. A total of 18 flocks out of 30 broiler flocks (60%) were positive for E. coli infection. On the base of the Congo red (CR) binding assay, 15 flocks out of 18 were identified as pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…It had been reported that more than 80% of colibacillosis outbreaks was associated with three serogroups (O78, O2, and O1) [18]. Additionally, APEC serogroup O78 was mostly isolated from colibacillosis cases in Egypt [19][20][21][22] and worldwide [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that more than 80% of colibacillosis outbreaks was associated with three serogroups (O78, O2, and O1) [18]. Additionally, APEC serogroup O78 was mostly isolated from colibacillosis cases in Egypt [19][20][21][22] and worldwide [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%